2016
DOI: 10.4014/jmb.1606.06008
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Chemical Structure and Antimicrobial Activities of Isothiocyanates from Cruciferous Vegetables against Oral Pathogens

Abstract: We evaluated the potentials of 10 isothiocyanates (ITCs) from cruciferous vegetables and radish root hydrolysate for inhibiting the growth of oral pathogens, with an emphasis on assessing any structure-function relationship. Structural differences in ITCs impacted their antimicrobial activities against oral pathogens differently. The indolyl ITC (indol-3-carbinol) was the most potent inhibitor of the growth of oral pathogens, followed by aromatic ITCs (benzyl ITC (BITC) and phenylethyl ITC (PEITC)) and aliphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 0 publications
0
40
3
Order By: Relevance
“…showed that E . faecalis is quite resistant to SFN and PEITC (MIC = 1 g/L or higher) 30 . Such discrepancy between MIC values might result from different strains and media used in our study compared with previously published work.…”
Section: Discussionmentioning
confidence: 99%
“…showed that E . faecalis is quite resistant to SFN and PEITC (MIC = 1 g/L or higher) 30 . Such discrepancy between MIC values might result from different strains and media used in our study compared with previously published work.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, their anti-microbial, anti-oxidant and anti-inflammatory properties are of particular importance. More specifically, the anti-microbial activity of ITCs has been documented in a number of studies, suggesting possible use of these compounds as natural antibiotic agents, food additives and/or pesticides [33,34,35,36,37,38,39]. It has been reported that they have both bacteriostatic and bactericidal potencies and many mechanisms have been suggested to mediate these properties.…”
Section: Introductionmentioning
confidence: 99%
“…Isothiocyanates have long been considered by the scientific community, for the numerous pharmacological properties demonstrated (Melchini et al, 2013;Lenzi et al, 2014). Several scientific studies have shown that 6-MITC in particular, possesses interesting antimicrobial (Hirokuni et al, 1998;Ko et al, 2016), anti-inflammatory (Uto et al, 2005;Uto et al, 2007;Uto et al, 2012), antiplatelet (Morimitsu et al, 2000) and antioxidant (Mizuno et al, 2011) properties.…”
Section: Introductionmentioning
confidence: 99%